Automated Synthesis of 1-Tetradecylphosphonic Acid-Capped FAPbBr3 Nanocrystals for Light Conversion in Display Applications - Hu, Huiying; Shi, Hongyang; Zhang, Jiyun; Hauch, Jens; Osvet, Andres; Brabec, Christoph (ACS Applied Nano Materials, 2024)
Perovskite nanocrystals (NCs) have garnered increasing attention as light-emitting materials owing to their high photoluminescence quantum yields (PLQY) and narrow full width at half-maximum (fwhm). However, the poor stability hinders their practical application in displays. In this work, we investigate the photostability of FAPbBr3 NCs with the modification of 1-tetradecylphosphonic acid (TDPA). Employing a high-throughput approach, the optimized FAPbBr3/TDPA NCs reached a sufficiently high PLQY of 76% with a narrow band emission of 20 nm, as opposed to 45% PLQY for FAPbBr3/oleic acid NCs. Due to the strong passivation of TDPA on the perovskite surface, NC-filled polymeric binder layers exhibit excellent photostability under environmental conditions. The optimal samples maintained 95% of the initial PL intensity after continuous intense irradiation.
CRIS-Team Scopus Importer:2024-04-26
Keywords: ligand; light conversion; perovskite nanocrystal; PLQY; stability